Onion peel color extract incorporation in pasta and effect on functional, phytochemical, structural, thermal, and storage stability - S. Abinaya; Anil Panghal; Navnidhi Chhikara; Priya Bishnoi; Ronak Tanwar; Ravi Gupta (Food Chemistry Advances)
Natural coloring extracts from agri-products had been proven rich in polyphenols, carotenoids and flavonoids, with enormous potential to be used as food colorant. In the present study, pasta products were prepared with onion peel color extract (0, 2, 4, 6, and 8 %) which led to remarkable increment in total phenol content (59.05 to 280.01 mg GAE/100 g), total flavonoid content (30.09 to 250.48 mg/100 g), and antioxidant activity (16.10 to 44.82 % DPPH activity). The gelatinization temperature of pasta was increased while enthalpy was declined with incorporation of color extract from waste onion peel, as reported by Differential Scanning Calorimetry. Scanning Electron Microscope images revealed disrupted and widely exposed starch granules resulting in a substantial higher gruel loss ranging from 4.55 % (control) to 6.33 % in pasta prepared with 8 % color extract from onion peel. This structural alteration is well supported by X-Ray Diffraction. Moreover, the structural disorganization of long amylopectin helices and amylose resulted in decreased peak, trough and final viscosities during Rapid Visco Analysis as the percentage of color extract increased. The optimal incorporated amount found for attaining better quality pasta with desired sensory attributes was found to be 4 % peel extract. By increasing the level of incorporation, the lightness and yellowness values were reduced, whereas the redness values were increased. There were no significant changes observed with cooking time, cooked weight, gruel solid loss, water solubility index and water absorption index of pasta over the storage period of >60 days.